2010
DOI: 10.1111/j.1551-2916.2010.03867.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Silicon Carbide Nanopowder Using Silica Fume

Abstract: Silica fume is a byproduct of producing silicon metal and ferrosilicon alloys, and contains 94–97 wt% SiO2. This study demonstrates, for the first time, that silica fume can be converted to nano‐SiC powder at 1500°C via carbothermic reduction with the aid of high‐energy ball milling of the silica fume plus graphite mixture at room temperature. The nano‐SiC synthesized has particle sizes as small as 30 nm. The effects of the carbothermic reduction temperature and the graphite concentration in the starting SiO2+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 31 publications
0
26
0
1
Order By: Relevance
“…However, the irregularly shaped particles were not observed on the surface of the SiCO ceramic. It is a reasonable assumption that the particles can react with residual carbon or CO. Zhong et al reported different reaction pathways of carbothermic reduction from silica [35]. It is well accepted that SiC formation from carbothermic reduction occurs through the following overall reaction (1).…”
Section: Decomposition Behavior Of the Pu Sponge And Polymeric Precursormentioning
confidence: 97%
“…However, the irregularly shaped particles were not observed on the surface of the SiCO ceramic. It is a reasonable assumption that the particles can react with residual carbon or CO. Zhong et al reported different reaction pathways of carbothermic reduction from silica [35]. It is well accepted that SiC formation from carbothermic reduction occurs through the following overall reaction (1).…”
Section: Decomposition Behavior Of the Pu Sponge And Polymeric Precursormentioning
confidence: 97%
“…Nano SiC have been studied intensively for high temperature structural applications, such as turbine and automobile engine components and heat exchangers, as well as energy applications [11,12]. Recently, using a process called as the integrated mechanical and thermal activation (IMTA) process, nano-SiC and SiC/Si 3 N 4 nanocomposite have been produced from silica fume at 1500 • C [13][14][15][16][17]. Since rice husk contains a higher silica content (15-20 wt.%), it should also be a promising material for producing nano SiC powder to reduce the cost of the starting raw materials, also while attaining the powder with nanostructures for advanced technology applications.…”
Section: Introductionmentioning
confidence: 99%
“…(i) cooking at lower temperature (400-800 • C) in a controlled manner to remove volatiles and (ii) reacting the cooked rice husk at high temperature (>1300 • C) to form SiC [1,[4][5]. The potential feature of rice husk is their high silica content (15)(16)(17)(18)(19)(20) wt.%) with small amount of alkalis and trace elements [6,7]. Heating the husks produces amorphous carbon as by-product of cellulose carbonization, while silica remains unchanged.…”
Section: Introductionmentioning
confidence: 99%
“…Although most of the processes resulted in highly uniform and homogeneously distributed composites, most of them require expensive starting materials or high cost equipment. Recently, using a process called as the integrated mechanical and thermal activation (IMTA) process, nano‐SiC has been produced from silica fume by subjecting the mixture of silica fume + graphite to carbothermal reduction and nitridation at 1500°C . The current method of production of nanostructured Si 3 N 4 /SiC composite powders differs from conventional carbothermal reduction and nitridation, in that the starting raw materials, silica fume and graphite, are mechanically activated at room temperature before subjecting them to the high‐temperature synthesis reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, using a process called as the integrated mechanical and thermal activation (IMTA) process, nano-SiC has been produced from silica fume by subjecting the mixture of silica fume + graphite to carbothermal reduction and nitridation at 1500°C. 23 The current method of production of nanostructured Si 3 N 4 / SiC composite powders differs from conventional carbothermal reduction and nitridation, 24 in that the starting raw materials, silica fume and graphite, are mechanically activated at room temperature before subjecting them to the high-temperature synthesis reaction. Due to the mechanical activation at ambient temperature, the IMTA process substantially reduces the reaction time and temperature required for the reaction, in addition to utilizing low cost starting raw materials.…”
Section: Introductionmentioning
confidence: 99%